Can jets make the radioactively powered emission from neutron star mergers bluer?. Issue 2 (28th October 2020) - Nativi, L; Bulla, M; Rosswog, S; Lundman, C; Kowal, G; Gizzi, D; Lamb, G P; Perego, A
ABSTRACT: Neutron star mergers eject neutron-rich matter in which heavy elements are synthesized. The decay of these freshly synthesized elements powers electromagnetic transients ('macronovae' or 'kilonovae') whose luminosity and colour strongly depend on their nuclear composition. If the ejecta are very neutron-rich (electron fraction Y e < 0.25), they contain fair amounts of lanthanides and actinides that have large opacities and therefore efficiently trap the radiation inside the ejecta so that the emission peaks in the red part of the spectrum. Even small amounts of this high-opacity material can obscure emission from lower lying material and therefore act as a 'lanthanide curtain'. Here, we investigate how a relativistic jet that punches through the ejecta can potentially push away a significant fraction of the high opacity material before the macronova begins to shine. We use the results of detailed neutrino-driven wind studies as initial conditions and explore with 3D special relativistic hydrodynamic simulations how jets are propagating through these winds. Subsequently, we perform Monte Carlo radiative transfer calculations to explore the resulting macronova emission. We find that the hole punched by the jet makes the macronova brighter and bluer for on-axis observers during the first few days of emission, and that more powerful jets have larger impacts on the macronova.